Foreword - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2017)
At the end of 2017, according to World Economic Forum Agenda, it seems that economic competitiveness matters, but not as an end in itself. It matters because nations that are more competitive are more productive, and are therefore more able to provide for the social needs of their people. The world has changed dramatically over the last decade, and measuring the factors that determine competitiveness continues to be a highly complex process. It is certainly true that the Fourth Industrial Revolution (4IR) – new, rapidly changing technologies in many different fields – has changed the way we need to measure some aspects of competitiveness, particularly in relation to innovation and ideas. We need to stress, for example, the value of ideas and collaboration within companies; the values of open-mindedness, of connectivity, and the value of an entrepreneurial spirit. And we have had to emphasize a new kind of education: one that is more conducive to students’ creativity, their ability to observe and generate ideas. The new industrial revolution, also known as the 4IR, has forced us to put more emphasis on all these aspects of a nation’s innovation ecosystem. The appearance of very disruptive technologies has been incredibly rapid. If we go back 10 years, the iPhone didn’t even exist. We have seen huge developments in artificial intelligence, new materials, synthetic biology, big data and on-demand technologies, and all these are changing the business landscape at a planetary level. Significantly, many of these innovations did not occur in those countries where technology used to be produced almost monopolistically. It is no longer the case that only the US and Europe innovate; the new industrial revolution has created opportunities for nations across the globe. This is a hugely important trend.